A Review of Alternative Energy Technologies - T. E. Walsh (Society for Mining, Metallurgy & Exploration, 1980)
I will address two important alternative energy resources, solar and geothermal, with emphasis on their potential application in electric power generation. As a result of this presentation, I hope to leave you with a realistic view of the principal technology options that are being developed or that are available. Solar Types of Collection In terrestrial solar applications, the biggest challenge is to find ways of collecting the sun’s relatively low intensity energy so it can be converted economically to useful thermal or electric energy. Fig. 1 shows that there are both natural and technological ways of collecting solar energy. In nature we find that solar energy aids in the production of biological growth, rainfall, and wind, all of which can, in one form or another, be put to use in the production of heat or electric power. The sun’s rays also are collected and stored naturally in the form of heat in the upper layers of the ocean which can be put to use in the production of electric energy by means of ocean thermal energy conversion (OTEC) approaches. On the technological side, the sun’s rays can be intercepted by materials that directly absorb and convert its energy to low-grade heat, or by mirrors or lenses that focus the rays onto a material to produce high-temperature heat. The higher temperature systems can be used to drive efficient heat engines in the production of electricityy. The sun’s rays also can be collected on photosensitive materials, in either a direct or concentrated form to generate DC electricity directly. The systems I will discuss employ all of these means of collection and conversion, excluding biological and hydroelectric. The former is too exi